Roll rate perceptual thresholds in active and passive curve driving simulation. (May 2016) - Nesti, Alessandro; Nooij, Suzanne; Losert, Martin; Bülthoff, Heinrich H; Pretto, Paolo
In driving simulation, simulator tilt is used to reproduce sustained linear acceleration. In order to feel realistic, this tilt is performed at a rate below the human tilt rate detection threshold, which is usually assumed constant. However, it is known that many factors affect the threshold, such as visual information, simulator motion in additional directions, or the driver's active effort required for controlling the vehicle. Here we investigated the effect of these factors on the roll rate detection threshold during simulated curve driving. Ten participants reported whether they detected roll motion in multiple trials during simulated curve driving, while roll rate was varied over trials. Roll rate detection thresholds were measured under four conditions. In the first three conditions, participants were moved passively through a curve with the following: (i) roll only in darkness; (ii) combined roll/sway in darkness; (iii) combined roll/sway and visual information. In the fourth (iv) condition participants actively drove through the curve. The results showed that roll rate thresholds in simulated curve driving increase, that is, sensitivity decreases, when the roll tilt is combined with sway motion. Moreover, an active control task seemed to further increase the detection threshold, that is, impair motion sensitivity, but with large individual differences. We hypothesize that this is related to the level of immersion during the task.